Geographically structured genetic and morphological variation in a new species of Cyrtodactylus (Squamata, Gekkonidae) from a karstic archipelago in western Cambodia - Evan S. H. Quah; L. Lee Grismer; Pablo Sinovas; Phyroum Chourn; Sophea Chhin; Seiha Hun; Anthony Cobos; Peter Geissler; Christian Ching; Matthew L. Murdoch; Sothearen Thi; Jeren J. Gregory; et al. (Pensoft Publishers, 2025)
A new species of karst-dwelling Bent-toed Gecko (genus Cyrtodactylus) is described from an unexplored karstic archipelago in western Cambodia. Cyrtodactylus kampingpoiensis sp. Nov. is composed of four allopatric, monophyletic mitochondrial lineages based on the ND2 gene. All are statistically diagnosable from one another based on univariate (ANOVA) and multivariate (PCA, DAPC, and MFA) analyses using a suite of size-correct- ed morphometric, meristic, and categorical color pattern and morphological characters. Uncorrected pairwise sequence divergence among them is low (1.4–2.2%), indicating a recent divergence from one another. Given their all-party, diagnosability, monophyly (i.e., no individuals from one population are embedded within another), we contend they are on separate evolutionary trajectories with no chance of secondary overlap via dispersal through the current unhabitual terrain or through the unlikely future coalescence of the karstic formations on which they occur. The discovery of this new species underscores the necessity for further exploration to gain a more informed understanding of the herpetological diversity of Cambodia in general, and that of western Cambodia in particular, where dozens of isolated karstic formations still remain unexplored.